2009
DOI: 10.1007/s10877-009-9209-5
|View full text |Cite
|
Sign up to set email alerts
|

The anaesthetic report: custom-made printouts from anaesthesia-information-management-systems using extensible stylesheet language transformation

Abstract: XSLT proved to be a very satisfactory technique to create different printouts and is therefore a feasible technique to enhance any AIMS. As XML turns out to be one of the most important formats for medical data, we call for the development of an international anaesthetic XML-standard and its adoption to AIMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…This controversial discussion is beyond the scope of this study. Multiple studies have demonstrated the utility of tools to improve the quality of communication during handover, both in the operating room 31,32 and in other areas of medicine. 33,34 It would seem plausible that reducing errors during information transfer could lead to safer care.…”
Section: Discussionmentioning
confidence: 99%
“…This controversial discussion is beyond the scope of this study. Multiple studies have demonstrated the utility of tools to improve the quality of communication during handover, both in the operating room 31,32 and in other areas of medicine. 33,34 It would seem plausible that reducing errors during information transfer could lead to safer care.…”
Section: Discussionmentioning
confidence: 99%
“…21 As part of the Safe Surgery Saves Lives campaign of the World Health Organization, a structured checklist used before induction of anesthesia, before incision, and before the patient leaves the operating room reduced mortality and complications by more than 35%. 11,26,27 With use of the electronic checklist, information for patient weight, airway management, IV access, estimated blood loss, urine output, and antibiotic administration was displayed from previous entries in the record, and several of these items showed statistically significant improvements in information transfer with use of the checklist. Studies of electronic health record-based tools in other areas of medicine have shown benefit in improving information transfer and reducing adverse events.…”
Section: Information Transfer and Retentionmentioning
confidence: 99%
“…If a hospital uses an electronic medical record -or if the anesthesia department has an Anesthesia Information Management System -it would seem logical to facilitate the handover and standardize the process by generating handover sheets by combining physician input with automatically extracted data from the system such as patient demographics, location (floor, ward, room), current medications, allergies, code status, etc. [16]. Handover sheets can be printed to be carried by the resident when rounding.…”
Section: Integrating Handover With the Electronic Medical Recordmentioning
confidence: 99%